Éclairages foucaldiens sur l’incrimination du déisme et de la libre pensée dans la jeune République américaine - Auréliane Narvaez (Transatlantica)
The development of deistical freethought, which appealed to a growing share of the American population at the turn of the nineteenth century, gradually became a matter of concern for the Protestant religious authorities that endeavored to counter its growth by targeting and incriminating it under the umbrella term of religious “infidelity.” Led by actors of orthodox and evangelical Protestantism alike, this unprecedented attack on deism relied on the vindication of disciplinary, social, as well as sanitary norms. To what extent can Foucault’s concepts of governmentality and biopolitics be conducive to a better understanding of the characteristics and mechanisms of this anti-infidel controversy? These assaults on religious infidelity framed deism as a multifaceted peril disrupting the stability of the young Republic, ultimately forging a form of Protestant governmentality that sought to make the population internalize the rejection of religious skepticism. Undermining deism thus hinged on security and sanitary discourses that associated religious infidelity with anarchy, criminality, and even insanity. Conflating religious and sexual infidelity also contributed to the development of a biopolitics of femininity and womanhood that presented freethought and the critique of religion as synonymous with licentiousness and moral depravity.